In situ nutritional assessment of diets with passion fruit meal (Passiflora edulis) as replacement of maize (Zea mays) - Sánchez Laíño, Adolfo Rodolfo (2019)
The parameters of in situ ruminal degradation of passion fruit meal (Passiflora edulis) included in diets for ruminants as replacement of maize were studied. A randomized complete block design was applied with four treatments (0, 10, 20 and 30% [T, T2, T3 and T4, respectively] of inclusion of passion fruit meal), three blocks (rumen-fistulated bovine) and seven incubation times (0, 3, 6, 12, 24, 48 and 72 hours). The differences between means were established using the Tukey test (p<0.05). T1 and T2 showed the highest (p<0.05) degradability of dry matter and organic matter at 48 and 72 h of incubation, respectively, while neutral detergent fibre and acid detergent fibre had a greater degradability in T4 and T3 at 48 and 72 h of incubation. The ruminal kinetics parameters were not significant in any of the variables evaluated. The results show that passion fruit meal can be used to replace maize up to 10% in diets for ruminants in the Ecuadorian littoral.